Exposition to Biological Control Agent Trichoderma stromaticum Increases the Development of Cancer in Mice Injected With Murine Melanoma - Santos, Uener R. dos; Costa, Marliete C.; de Freitas, Gustavo J. C.; de Oliveira, Flávia S.; Santos, Bianca R.; Silva, Juneo F.; Santos, Daniel A.; Dias, Adriana A. M.; de Carvalho, Luciana D.; Augusto, Danillo G.; dos Santos, Jane L. (Frontiers in Cellular and Infection Microbiology, 2020)
Biological control agents (BCA) are an alternative to chemical pesticides and an emerging strategy to safely eliminate plant pathogens. Trichoderma spp. are the most common fungi used as BCAs. They produce spores that are released into the air and can potentially interact with immune system of mammals. We previously showed that Trichoderma affects expression of genes encoding pattern recognition receptors (PRRs) and cytokines in mice. PRRs are involved in the recognition of microorganisms and can lead to pro-tumoral signaling. Here, we evaluated if mice injected with low doses of murine melanoma exhibited increased development of lung tumor when treated with conidia of T. stromaticum. Mice treated with T. stromaticum and inoculated with B16-F10 melanoma cells exhibited significant increase in tumor uptake (p = 0.006) and increased number of visible nodules in the lungs (p = 0.015). We also analyzed mRNA expression levels of genes encoding PRRs in lung of mice exposed to T. stromaticum and demonstrated that mice treated with T. stromaticum conidia exhibited lower expression levels of Clec7a and increased expression of Tlr4 (toll like receptor 4) compared to non-treated controls. The expression levels of Clec7a and Tlr2 were increased in mice treated with T. stromaticum and inoculated with murine melanoma compared to controls only inoculated with melanoma. Our results demonstrate that intranasal exposition to T. stromaticum increases tumor in the B16-F10 model, which may raise concerns regarding the safety of its use in agriculture.